2021
DOI: 10.1002/smll.202103005
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell CoSe2/WSe2 Heterostructures@Carbon in Porous Carbon Nanosheets as Advanced Anode for Sodium Ion Batteries

Abstract: Therefore, in response to the above issues, the most urgent and crucial task is to develop novel anode materials with special crystal design, aiming to improve the kinetics of sodiation and desodiation, which mainly comprises the finding of new materials and the structural design and morphology control of materials. [5] So far, transition metal chalcogenides, consisting of transition metal oxides, [6] transition metal sulfides, [7] and transition metal selenides, [8] have been considered as promising anode mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 61 publications
(60 reference statements)
3
44
0
Order By: Relevance
“…It is remarkable that, compared with the other reported CoS 2 or CoSe 2 -based anodes, the CNF@CoSSe@C electrode still exhibits overwhelming advantages in terms of rate performance, especially at a rate over 5.0 A g −1 . 16,45–58 Except for the high capacity and superior rate capability, a qualified electrode should also possess ultrastable cyclic stability at a high rate to ensure long-term Na + -storage and release. Experiencing an ultralong de-/sodiation progress up to 13 000 cycles, the reversible capacity of the CNF@CoSSe@C electrode remains as high as 158.2 mA h g −1 with a decaying capacity rate of only 0.01% for each cycle.…”
Section: Resultsmentioning
confidence: 99%
“…It is remarkable that, compared with the other reported CoS 2 or CoSe 2 -based anodes, the CNF@CoSSe@C electrode still exhibits overwhelming advantages in terms of rate performance, especially at a rate over 5.0 A g −1 . 16,45–58 Except for the high capacity and superior rate capability, a qualified electrode should also possess ultrastable cyclic stability at a high rate to ensure long-term Na + -storage and release. Experiencing an ultralong de-/sodiation progress up to 13 000 cycles, the reversible capacity of the CNF@CoSSe@C electrode remains as high as 158.2 mA h g −1 with a decaying capacity rate of only 0.01% for each cycle.…”
Section: Resultsmentioning
confidence: 99%
“…The abundant lattice mismatch and defects formed at heterogeneous interfaces change the reaction kinetics and long-range disorder, further affect the transport behavior of carriers. [21][22][23] The diverse redox potentials and out-of-step electrochemical reactions of different components alleviate volumetric strains during intercalation/extraction processes of Na + . [23] Constructing hierarchical micro/nanostructures as anodes for sodium ion batteries is an important approach for exploiting efficient energy storage devices.…”
Section: Doi: 101002/smll202107370mentioning
confidence: 99%
“…[19][20][21][22] For example, Zhang et al fabricated CoSe 2 /WSe 2 @C/CN heterostructures as anodes for SIBs, which could achieve a remarkable cyclic stability of 277 mA h g À1 at 0.5 A g À1 aer 200 cycles. 23 Yang's group designed SnSe 2 /FeSe 2 @NC, which could achieve an outstanding rate performance of 345 mA h g À1 at 20 A g À1 as Na storage anodes. 24 Wang's group reported that NiSe 2 @-C@MXene could deliver a remarkable cyclic stability of 327 mA h g À1 aer 4000 cycles at 2 A g À1 .…”
Section: Introductionmentioning
confidence: 99%